Influence of ultrasound on alkaline treatment of empty fruit bunch fibre: preliminary study - Wan Mohd Eqhwan, Iskandar; Ong, Huei Ruey; Khan, Md. Maksudur Rahman; Ridzuan, Ramli; Rohaya, Mohamed Halim (IOP Publishing, 2021)
This research underlines the effect of ultrasound in NaOH surface modification of empty fruit bunch (EFB) fibre. Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were used to characterized the fibres. It can be seen that surface morphology treated by ultrasound assisted alkali treatment shows smooth surface with minor impurities. Additionally, the elimination of hemicellulose on EFB fibre surface can be proven by the disappearance of peak between 2900-1700 cm−1 (C-H). Furthermore, Ultrasound assisted alkali method demonstrate the admirable value (300 N/mm2) in enhancing the tensile stress of EFB fibre and comparable with alkali soaking technique (292 N/mm2). The findings indicate that ultrasound-assisted alkali treatment has the potential to be used as surface modification method in the industry.